Deutschland and the sea why the future of the Bundeswehr is on the high seas - Speckmann, Thomas 1974- (IP / Global edition, 2011)
Modernizing an army and simultaneously saving money requires setting strict priorities. But how? For Germany, future deployments will require a strong navy - an unsurprising truism since more than 80 percent of world trade occurs on the sea. When will Berlin finally start to think about its maritime capabilities? (DGAP-IP/GE)